Navigating Village Financial Effectiveness: The Role of Competence, Participation, Budget Transparency and Leadership Commitment in Village Financial Management - Ni Nyoman Selviana; Nina Yusnita Yamin; Haryono P. Kamase; Latifah Sukmawati Yuniar; Arif Gunarsa (SAINTIS Publishing, 2025)
This study intends to analyze the determining factors of effective village financial management, namely Competence of Apparatus, Community Participation, and Budget Clarity. Crucially, this study also discusses function Leadership Commitment be a moderator of these relationships. Effective village financial management is a key pillar of successful village development and the achievement of public accountability. Using a quantitative approach, data were obtained from questionnaires distributed to 200 village government officials in Sigi Regency, Central Sulawesi. The data was analyzed using the Structural Equation Modeling (SEM) method using Partial Least Squares (PLS) technique. The study findings indicate that Official Competence, Community Participation, and Budget Clarity have been partially proven to have a positive and significant impact on the effectiveness of village financial management. This study also found that leadership commitment significantly strengthens the influence of Competence of Apparatus and Community Participation in the effectiveness of village financial management. However, leadership commitment does not play a strong role ties between fund transparency and the effectiveness of village financial management. These findings indicate that the competence of the apparatus ensures accuracy and compliance with technical procedures, community participation creates social control and legitimacy, and transparency in budgeting is important. The implications of this study suggest that human and ethical factors are more influential in optimizing social factors.